Pengembangan Sensor IOT Untuk Monitoring Kualitas Udara di Area Perkantoran - Suherman, Reza Bintang; Sekti, Binastya Anggara (Ikatan Ahli Informatika Indonesia, 2024)
Air pollution poses a significant threat to public health and the environment. To address this issue, the development of Internet of Things (IoT)-based air quality monitoring systems has gained prominence. This study aims to design and analyze an IoT-based system capable of real-time monitoring of various air quality parameters such as PM 2.5, CO, CO2, temperature, humidity, and air pressure. Through a literature review and conceptual system design, the study identifies the potential of IoT-based systems in improving air quality understanding and decision-making. However, challenges including sensor advancement, reliable connectivity, power infrastructure, and data security must be overcome. By addressing these challenges, IoT-based air quality monitoring systems can play a crucial role in maintaining healthy air quality for communities.